2023
DOI: 10.3390/insects14050405
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito Blood Feeding Prevention Using an Extra-Low DC Voltage Charged Cloth

Abstract: Mosquito vector-borne diseases such as malaria and dengue pose a major threat to human health. Personal protection from mosquito blood feeding is mostly by treating clothing with insecticides and the use of repellents on clothing and skin. Here, we developed a low-voltage, mosquito-resistant cloth (MRC) that blocked all blood feeding across the textile and was flexible and breathable. The design was based on mosquito head and proboscis morphometrics, the development of a novel 3-D textile with the outer conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…Phlebotomus papatasi larvae and pupae (stages L3 and pupae P. papatasi , Turkey strain PPTK, NR-44000) were obtained from the Walter Reed Army Institute of Research, BEI Resources, NIAID, NIH (American Type Culture Collection, 10,801 University Blvd., Manassas, VA, USA) and maintained through the adult stage under Level II biological containment (ACL-2, arthropod) in the Dearstyne Entomology Laboratory (3230 Ligon Street, North Carolina State University, Raleigh, NC, USA) by methods approved by NCSU Environmental Health and Public Safety (BUA #2019-10-818). Larval pots were placed in a plexiglass (30.48 × 30.48 × 30.48 cm) mosquito rearing cage [ 17 ], housed in a foldable butterfly rearing cage (Restcloud, Chengdu, China) in a walk-in incubator (maintained at 26 °C, 80% relative humidity, and 12:12 (L:D) cycle). The incubator was in a room in the Dearstyne Entomology Building, where the only access door was nominally closed and where the door opening into the room was covered with mosquito netting.…”
Section: Methodsmentioning
confidence: 99%
“…Phlebotomus papatasi larvae and pupae (stages L3 and pupae P. papatasi , Turkey strain PPTK, NR-44000) were obtained from the Walter Reed Army Institute of Research, BEI Resources, NIAID, NIH (American Type Culture Collection, 10,801 University Blvd., Manassas, VA, USA) and maintained through the adult stage under Level II biological containment (ACL-2, arthropod) in the Dearstyne Entomology Laboratory (3230 Ligon Street, North Carolina State University, Raleigh, NC, USA) by methods approved by NCSU Environmental Health and Public Safety (BUA #2019-10-818). Larval pots were placed in a plexiglass (30.48 × 30.48 × 30.48 cm) mosquito rearing cage [ 17 ], housed in a foldable butterfly rearing cage (Restcloud, Chengdu, China) in a walk-in incubator (maintained at 26 °C, 80% relative humidity, and 12:12 (L:D) cycle). The incubator was in a room in the Dearstyne Entomology Building, where the only access door was nominally closed and where the door opening into the room was covered with mosquito netting.…”
Section: Methodsmentioning
confidence: 99%
“…Selain itu, tegangan arus listrik pada prototipe alat ini aman untuk manusia seperti yang dijelaskan penelitian sebelumnya bahwa tegangan 7 volt arus listrik DC yang diaplikasikan pada pakaian yang berfungsi sebagai proteksi nyamuk masih aman ketika diaplikasikan. 14 Berdasarkan latar belakang tersebut, penelitian ini menganalisis pengaruh penggunaan arus listrik DC sebagai daya kejut terhadap kematian larva Ae. aegypti.…”
Section: Pendahuluanunclassified
“…Many studies have suggested the role of plant-based therapy against blood-borne parasites, which are under development and further require in vivo studies (Kaur et al, 2021;Qureshi, 2021;Kamaraj et al, 2022;Benlarbi et al, 2023;Wulandari et al, 2023). Apart from drug treatment strategies, various preventive measures are required to control the spread of these zoonotic infections worldwide (Molyneux, 2006;Ghodsi et al, 2019;Luan et al, 2023).…”
Section: Introductionmentioning
confidence: 99%